The end of getting lost : [large type] a novel - Kirman, Robin (Center Point Large Print, 2022)
"The year is 1996 - a time before cell phones, status updates, and location tags - when you could still travel to a remote corner of the world and disappear, if you chose to do so. This is where we meet Gina Reinhold and Duncan Lowy, a young artistic couple madly in love, traveling around Europe on a romantic adventure. It's a time both thrilling and dizzying for Gina, whose memories are hazy following a head injury - and the growing sense that the man at her side, her one companion on this strange continent, is keeping secrets from her. Just what is Duncan hiding and how far will he go to keep their pasts at bay? As the pair hop borders across Europe, their former lives threatening to catch up with them while the truth grows more elusive, we witness how love can lead us astray, and what it means to lose oneself in love . . ."--